Using a Situation Awareness Approach to Identify Differences in the Performance Profiles of the World’s Top Two Squash Players and Their Opponents - Murray, Stafford; James, Nic; Perš, Janez; Mandeljc, Rok; Vučković, Goran (Frontiers in Psychology, 2019)
Purpose: The pressure exerted on a squash player is a consequence of the quality of a shot coupled with the ability of the player to return the ball i.e. the coupling of the two players’ situation awareness (SA) abilities. SA refers to an awareness of all relevant sources of information, the ability to synthesise this information using domain knowledge and the ability to physically respond to a situation. Methods: Matches involving the two best players in the world (n = 9) at the 2011 Rowe British Grand Prix, held in Manchester, UK were recorded and processed using Tracker software. Shot type, ball location, players’ positions on court and movement parameters between the time an opponent played a shot prior to the player’s shot to the time of the opponent's following shot were captured 25 times per second. All shots (excluding serves and rally ending shots) produced five main SA clusters, similar to those presented by Murray et al. (2018), except a greater proportion of shots were categorised in the greater pressure clusters and less in the lower pressure ones. Results: Individual matches were presented using cluster performance profile infographics which demonstrated how individual player’s performance profiles differed between matches. Conclusion: It is suggested that it is the coupling, of the two player’s behaviours, that makes the examination of tactics so challenging. This inherently means that performance profiles vary in subtle ways, making consistent profiles that are independent of the opponent very unlikely for elite players. This approach should be further modified to determine within match changes in performance.